2017
DOI: 10.4103/ijo.ijo_147_17
|View full text |Cite
|
Sign up to set email alerts
|

Needle stick injuries in a tertiary eye-care hospital: Incidence, management, outcomes, and recommendations

Abstract: Purpose:The purpose of this study is to assess the incidence, management, and outcomes for needle stick injuries (NSIs) in a tertiary eye-care hospital and provide appropriate recommendations for its prevention.Methods:This was a retrospective database review of NSI recorded between 2010 and 2015 at a tertiary eye care center. All staff members who had NSI were managed with standard treatment protocol. The mode, location, health-care workers affected and/or at risk for NSI were analyzed.Results:One hundred and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 11 publications
0
17
0
Order By: Relevance
“…The reported incidence of needlestick injury in eye care in India is 0.07/1000 surgeries. [ 9 ] This means one needlestick injury would result after 14,286 ocular surgeries. The transmission (seroconversion) risk after percutaneous exposure averages 0.3% for HIV, 1.8% for HCV, and 6%–30% for HBV.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The reported incidence of needlestick injury in eye care in India is 0.07/1000 surgeries. [ 9 ] This means one needlestick injury would result after 14,286 ocular surgeries. The transmission (seroconversion) risk after percutaneous exposure averages 0.3% for HIV, 1.8% for HCV, and 6%–30% for HBV.…”
Section: Resultsmentioning
confidence: 99%
“…[ 8 ] The reported incidence of needlestick injury in eye care in India is 0.07/1000 surgeries. [ 9 ] The prevalence of these blood-borne viral infections is on the rise, and the World Health Organization (WHO) reported that 252 million people are infected with HBV and 71 million with HCV. [ 10 ] The WHO estimates that HIV has infected 36.7 million people globally.…”
mentioning
confidence: 99%
“…recently reported that the average annual incidence of needle-stick injuries (NSIs) among HCWs at a tertiary eye care center over a 6-year period was 23/year (almost 2 per month). [ 2 ] Yet, another report from one of the nation's busy multispecialty hospitals presented more alarming data. About 80% of HCWs in this particular institute reported one or more NSIs in their career, of which 17.6% involved a patient with known history of HIV, HBV, or HCV or intravenous drug use.…”
mentioning
confidence: 99%
“…The costs of testing both HCW and patient after a NSI, postexposure prophylaxis, and the emotional strain suffered by HCW during this period are estimated to be significant. [ 2 ] Sometimes, the surgeries in these camps are performed sequentially without changing phacoemulsification tips risking disease transmission to other patients. The main argument in favor of universal screening is that foreknowledge of the patient's serological status will make the HCW alert, and implement safe practices known as universal precautions.…”
mentioning
confidence: 99%
“…[ 6 ] Use of ultra-sharp and short microsurgical instruments and sutures, working with high magnification, restricted visible surgical field while operating with a microscope, and suboptimal ambient illumination increase the relative risk of NSI in an ophthalmic surgical setting. [ 5 6 7 ] About 8% of vitreoretinal surgeons have reported NSI during the procedure of intravitreal injection. [ 8 ] Incidence of NSI in a tertiary care eye hospital in India was reported to be 0.07/1000 surgeries.…”
mentioning
confidence: 99%